Application of metagenomic next-generation sequencing in suspected intraocular infections. Issue 1 (January 2023) - Qian, Zhuyun; Zhang, Yankun; Wang, Lu; Li, Ziqiang; Wang, Hui; Kang, Hao; Feng, Jing; Hu, Xiaofeng; Tao, Yong
Purpose: To evaluate the efficacy of metagenomic next-generation sequencing (mNGS) and to explore its value in the diagnosis of intraocular infection. Methods: A retrospective case-series study of patients with suspected intraocular infection was performed. Intraocular fluid samples were collected from all the patients and sent for mNGS. Detailed clinical data, the results of mNGS and other laboratory examinations, the sequencing data of mNGS, and the final diagnosis were recorded. Results: Fifteen eyes of 15 patients were included in the study. Eight samples were identified as positive for different kinds of pathogens by mNGS, which were all confirmed by other laboratory examinations or effective diagnostic treatment. The mNGS results were negative in seven samples. The final diagnosis was still intraocular infection in four of the seven negative results. Of these, one patient was diagnosed with fungal endophthalmitis according to the clinical characteristics and good treatment response to the anti-fungal therapy, one patient underwent vitrectomy and the bacterial culture of the vitreous sample was positive for Brucella melitensis, and two patients were diagnosed with ocular tuberculosis according to the positive T-SPOT test and effective anti-tuberculous treatments. Conclusions: mNGS could be helpful in determining pathogens in cases of suspected intraocular infection. The mNGS protocols should be optimized for the detection of intracellular bacterial and fungal pathogens.